2014
DOI: 10.1159/000369963
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Follicular Lymphoma after Treatment for Invasive Squamous Cell Carcinoma

Abstract: Backgrounds/Aims: The authors describe the case of a 79-year-old Caucasian woman who presented an ocular adnexal lesion as the first clinical manifestation of a systemic follicular lymphoma, highlighting the clinicopathological features of this rare entity and its potential to be misdiagnosed as marginal zone lymphoma of the mucosa-associated lymphoid tissue. Methods: Conjunctival impression cytology was performed for a rapid initial diagnosis of lymphoma, and subsequent histopathological and immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(16 reference statements)
1
0
0
Order By: Relevance
“…The differentiation of histological types is also crucial for diagnosing lymphoma, as different lymphomas exhibit different behaviors and outcomes [30]. Along with previous reports, our current results showed that the main composition of POAL was MALT, followed by DLBCL [31][32][33].…”
Section: Discussionsupporting
confidence: 82%
“…The differentiation of histological types is also crucial for diagnosing lymphoma, as different lymphomas exhibit different behaviors and outcomes [30]. Along with previous reports, our current results showed that the main composition of POAL was MALT, followed by DLBCL [31][32][33].…”
Section: Discussionsupporting
confidence: 82%